National Guidelines for Trauma-Aware Education in Australia - Howard, Judith; L’Estrange, Lyra; Brown, Meegan (Frontiers in Education, 2022)
The National Guidelines for Trauma-Aware Education in Australia were developed in response to a rapidly growing interest in trauma-aware education across the country and to address the lack of site and system level guidance for application of trauma-aware practices in schools and early childhood services. Although research into trauma-aware education was increasing and resources and training and support programs were being developed across Australia, there were no nationally agreed guidelines providing consistency to thinking, policy, and practice. Drawing from public health and health promotion models for establishing guidelines for trauma-aware policy and practice, the Guidelines were developed through a thorough process of incorporating research evidence and expert and end-user input. The Guidelines were developed across 2017 to 2019 and finalized in 2021 and provide an important first step in a national response to trauma-aware education in Australia. This article will describe the “story” behind the development of the Guidelines. It is hoped that this “story” will help others considering development of systemic resources to inform the establishment and enhancement of trauma-aware policy and practice in schools and early childhood education services.